IMPROVEMENT OF NETWORK SURVIVABILITY USING THE EFFECTIVE REDUNDANCY DESIGN - Akhmad Wahyu Dani; Fadli Sirait; Fina Supegina; Rohilah Sahak; Kresna Jery Kusnanto (Universitas Mercu Buana, 2019)
Network survivability is a very important issue due to the sustainability of the network services. Failure in a network system conduce to disturbance of the network services and causes trouble to millions of applications. Implement an effective redundancy design is one of method to cope nuisance in terms of sustainability in a network. In this paper, there are two design networks with and without redundancy respectively by Metro Ethernet-based technique to support transmission of data and voice. Furthermore, there is a validation performance of networks by measuring and comparing the throughput, latency and jitter between the two network designs. The value of bandwidth capacity is 100 Mbps as plan bandwidth link. Measurements results denote that network with redundancy design is able to enhance performance of the network, the parameters are: the throughput on single link tends to moderate (25%-50%), on the other hand, the throughput values on the main link and back uplink are in accordance with very good condition (75%-100%). The values of frame loss ratio 69.979% - 56.679% (single link), 6.77% -9.999% (main link) and 6.676 %-9.999% (back uplink). The values of jitter and latency in network with redundancy design are much better than in single link network. The recovery time for each frame length is ranging from 48.999ms to 49.887ms, where it is still meet with the standard that must below 50ms. Finally, when the main link in the network topology with redundancy design undergo link fails condition, the backup link is able to maintain the quality of network throughout that time, on the contrary, network topology without redundancy design is unable.